Chapter 15 Urban Mobilities in Francophone African Return Narratives - Toivanen, Anna-Leena (Taylor & Francis, 2023)
This chapter discusses the representation of West and Central African cities in Francophone African narratives of diasporic return. Using as case studies Camara Laye's Dramouss (A Dream of Africa; 1966), Aïssatou Cissokho's Dakar, la touriste autochtone ("Dakar, the Native Tourist"; 1986), and Daniel Biyaoula's L'Impasse ("The Impasse"; 1996), the chapter focuses on the texts' portrayals of urban mobility practices and transport to explore the role of mobility in the construction of the postcolonial African city as experienced by the diasporic returnee, typical a displaced postcolonial mobile subject. In the discussed novels, various modes of mobility move the protagonists around in their former hometowns, permitting encounters with city dwellers and formerly familial urban landscapes. The texts' portrayals of the returnees' urban mobilities highlight the tensions between memory and the present and underline the protagonists' sense of unbelonging and disillusionment. By focusing on African cities from the perspective of urban mobilities, the chapter contributes to the on-going postcolonialization of literary urban studies and enhances the field's dialogue with mobilities research.